Evaluasi Kerusakan DNA Spermatozoa Semen Cair Babi Menggunakan Pewarnaan Toluidine Blue - Parera, Hermilinda; Lenda, Victor; Foeh, Nancy Diana; Sirat, Muhammad Mirandy Pratama (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
The integrity of the deoxyribonucleic acid (DNA) in sperm plays a crucial role in the fertilization process and embryonic development. This study aimed to evaluate the level of the DNA fragmentation of boar sperm in tris-citrate-fructose extender preserved at temperatures between 16-18°C for 3 days. The level of sperm DNA damage was analysed using toluidine blue (TB) staining. Pig semen collected from 4 male pigs aged 1.3-1.8 years was used as the research sample. Semen collected was conducted twice a week. The experimental method using a Completely Randomized Design with 4 storage duration groups as follows: Group I (0 hours of storage), Group II (24 hours of storage), Group III (48 hours of storage), and Group IV (72 hours of storage), each with 5 replications. The data were analysed using analysis of variance (ANOVA) and, if significant differences were found, Duncan's test was performed. The results of the evaluation of the percentage of DNA damage during the storage process at 16-180C at 0 hours, 24 hours, 48 hours and 72 hours was: 0.33 ± 1.66%, 0.80 ± 0.447%, 1.60 ± 1.14% and 2.80 ± 0.447%, respectively. These results demonstrate that liquid boar semen preserved with tris citrate fructose extender at 16-18 °C for 3 days has spermatozoa DNA damage levels within the normal range, making it suitable for artificial insemination and ensuring optimal AI success.